Kontroversi Juru Bicara Presidensi G20 Indonesia: Kajian Analisis Wacana Kritis Sara Mills - Tesalonika Hasugian; Patricia Robin (MUKASI: Jurnal Ilmu Komunikasi, 2023)
Bloomberg international media has published the news about Maudy Ayunda titled “G-20 Role for 27-year-old Indonesia Singer Sparks Criticism”. The news contains controversy about Maudy Ayunda’s role as a spokesperson of G20 Indonesia. The purpose of this research to answer the study problem is a critical discourse analysis of Sara Mills on the media text Bloomberg about the controversial spokesperson of G20 Indonesia. This research uses qualitative descriptive methods. Data analysis was carried out by text analysis based on critical discourse by Sara Mills emphasis on women’s discourse. Based on the results of the analysis in this study, Bloomberg international media has focused on an economic global rubric. The researcher found Sara Mills critical discourse analysis in the position of social actors: (1) The position of the subject which cornered the role of objects in the form of marginalization and stereotype discrimination; (2) The object's position has no chance to tell herself; (3) The reader's position tends to be directed by the journalist's perspective to feel concerned about the Indonesian government's decision to rush to take human resources from Indonesian youth who are not ready to play an active role in the country's economic and political world.